Managing the sovereign-bank nexus - Giovanni Dell'Ariccia; Caio Ferreira; Nigel Jenkinson; Luc Laeven; Alberto Martin; Camelia Minoiu; Alexander Popov (European Central Bank (ECB), 2018)
This paper identifies the various channels that give rise to a "sovereign-bank nexus" whereby the financial health of banks and sovereigns is intertwined. We find that banks and sovereigns are linked by three interacting channels: banks hold large amounts of sovereign debt; banks are protected by government guarantees; and the health of banks and governments affect and is affected by economic activity. Evidence suggests that all three channels are relevant. The paper concludes with a discussion of the policy implications of these findings.
Keywords: E62; F34; G01; G21; 330; fiscal policy; sovereign risk; financial stability; financial crisis; sovereign-bank nexus